A spectroscopic and photometric investigation of the mercury–manganese star KIC 6128830. Issue 2 (20th November 2017) - Hümmerich, Stefan; Niemczura, Ewa; Walczak, Przemysław; Paunzen, Ernst; Bernhard, Klaus; Murphy, Simon J; Drobek, Dominik
Abstract: The advent of space-based photometry provides the opportunity for the first precise characterizations of variability in mercury–manganese (HgMn/CP3) stars, which might advance our understanding of their internal structure. We have carried out a spectroscopic and photometric investigation of the candidate CP3 star KIC 6128830. A detailed abundance analysis based on newly acquired high-resolution spectra was performed, which confirms that the star's abundance pattern is fully consistent with its proposed classification. Photometric variability was investigated using 4 yr of archival Kepler data. In agreement with results from the literature, we have identified a single significant and independent frequency f 1  = 0.2065424 d −1 with a peak-to-peak amplitude of ∼3.4 mmag and harmonic frequencies up to 5 f 1 . Drawing on the predictions of state-of-the-art pulsation models and information on evolutionary status, we discuss the origin of the observed light changes. Our calculations predict the occurrence of g-mode pulsations at the observed variability frequency. On the other hand, the strictly mono-periodic nature of the variability strongly suggests a rotational origin. While we prefer the rotational explanation, the present data leave some uncertainty.